50 great myths of human sexuality - Schwartz, Pepper; Kempner, Martha (Wiley-Blackwell, 2015)
There are many misconceptions about human sexuality, and some are so misleading as to be dangerous. Schwartz and Kempner dispel commonly accepted myths and misunderstandings, covering areas from pre-marital sex and sexual diseases to body image.